Recombination dynamics of type-II excitons in (Ga, In)As/GaAs/Ga(As, Sb) heterostructures. (1st December 2016) - Gies, S; Holz, B; Fuchs, C; Stolz, W; Heimbrodt, W
Abstract: (Ga, In)As/GaAs/Ga(As, Sb) multi-quantum well heterostructures have been investigated using continuous wave and time-resolved photoluminescence spectroscopy at various temperatures. A complex interplay was observed between the excitonic type-II transitions with electrons in the (Ga, In)As well and holes in the Ga(As, Sb) well and the type-I excitons in the (Ga, In)As and Ga(As, Sb) wells. The type-II luminescence exhibits a strongly non-exponential temporal behavior below a critical temperature of T c  = 70 K. The transients were analyzed in the framework of a rate-equation model. It was found that the exciton relaxation and hopping in the localized states of the disordered ternary Ga(As, Sb) are the decisive processes to describe the dynamics of the type-II excitons correctly.